Quality of sleep and associated factors among healthcare providers during COVID-19 in Malaysia: a web-based cross-sectional study - Ching, Siew-Mooi; Ismail, Irmi Zarina; Cheong, Ai Theng; Yee, Anne; Thurasamy, Ramayah; Lim, Poh Ying; Supian, Ziti Akthar; Azmi, Siti Umi Fairuz; Ng, Jun Ying; Koh, Wen Ming; Ismail, Noor Diana; Lee, Kai Wei; et al. (Universiti Putra Malaysia Press, 2023)
Introduction: COVID-19 has placed enormous strain on healthcare providers (HCPs). This study aimed to determine the quality of sleep (QoS), and associated factors, of HCPs in primary care clinics during the COVID-19 pandemic. Methods: This was a web-based cross-sectional study of HCPs from 30 primary care clinics in Malaysia. QoS was assessed using a validated single-item scale, and the response ranged from 0 (poor) to 10 (excellent). SPSS version 26 was used for the analysis. Results: Our study included 1280 respondents. The mean QoS score was 6.725 = 1.961. One demographic factor that was positively associated with QoS was age. Having one workplace, nurse, medical assistant, medical laboratory technician (or healthcare assistant compared to being a driver, were also significantly positively associated with QoS. Personality factors that were significantly positively associated with QoS were HCPs’ abilities to cope with work stress and be altruistic. There were negative correlations between QoS and being a male HCP, concern about COVID-19 mortality and perceived risk of exposure to COVID-19. Conclusion: HCPs with clinical roles who were older, had a single workplace, were altruistic and could cope with work stress had better QoS. To maintain the QoS of HCPs, healthcare organisations should promote regular activities supporting the staffs’ mental health and encourage compassion for the organisation and an altruistic work culture, especially among younger employees.